Absence of detectable effect of radiotherapy and chemotherapy for breast cancer on the presence of low voltage areas in patients receiving left atrial catheter ablation. Issue 10 (5th November 2021) - Hashiguchi, Naotaka; Schenker, Niklas; Rottner, Laura; Reißmann, Bruno; Rillig, Andreas; Maurer, Tilman; Lemes, Christine; Kuck, Karl-Heinz; Ouyang, Feifan; Mathew, Shibu
Abstract: Purpose: Radiation and chemotherapy for breast cancer are known to cause side effects to the heart. However, it still remains unclear whether those therapies affect left atrium fibrosis. We sought to examine the effects of radiation and chemotherapy on the electroanatomic features of the left atrium (LA) in patients who received catheter ablation for LA arrhythmias and underwent radiation and/or chemotherapy prior to the procedure. Methods and results: We compared 38 patients who underwent catheter ablation for LA arrhythmias and had a previous diagnosis of breast cancer with 38 patients without breast cancer. LA low voltage zones (LVZ) were analysed during the electrophysiological (EP) study. The existence of LA LVZ did not differ significantly between both groups (71.1% vs. 76.3%, p = .602; 13.7cm 2 (IQR 0;20.6cm 2 ) vs. 7.0cm 2 (IQR 1.6;21.1cm 2 ), p = .690). Also scar distribution revealed no difference between both groups. However, an involvement of the anterior wall was common in both groups (65.8% vs. 73.7%, p = .454). Patients with breast cancer and persistent AF showed a trend towards greater LA scar areas 14.5% vs. 6.9%, p = .383) compared to the control group. Age and LA volume index were the only independent predictors for greater LA scarring. Conclusions: Thoracic irradiation and chemotherapy for breast cancer do not lead to an increase in LA scar area or a changed distribution of LA scarring. However, patient with breast cancer showed a tendency towards greater LA scar areas. Patient's age and LA volume index were identified as independent predictors for LA scar development.